Writing a proposal for your dissertation guidelines and examples - Terrell, Steven R. (The Guilford Press, 2016)
"This user-friendly guide helps students get started on--and complete--a successful doctoral dissertation proposal by accessibly explaining the process and breaking it down into manageable steps. Steven R. Terrell demonstrates how to write each chapter of the proposal, including the problem statement, purpose statement, and research questions and hypotheses; literature review; and detailed plan for data collection and analysis. Of special utility, end-of-chapter exercises serve as building blocks for developing a full draft of an original proposal. Numerous case study examples are drawn from across the social, behavioral, and health science disciplines. Appendices present an exemplary proposal written three ways to encompass quantitative, qualitative, and mixed-methods designs. Pedagogical Features: *"Let's Start Writing" exercises leading up to a complete proposal draft. *"Do You Understand" checklists of key terms plus an end-of-book glossary. *End-of-chapter quizzes with answers. *Case study examples from education, psychology, health sciences, business, and information systems. *Sample proposal with three variants of the methods chapter: quantitative, qualitative, and mixed methods"--